Uji Aktivitas Hipoglikemik Ekstrak Etanol Daun Kersen (Muntingia calabura L.) Terhadap Mencit (Mus musculus) Yang Diinduksi Aloksan - Zulham Zulham; Wahyu Hendrarti; Nurul Wahyuni (Jurnal Farmasi dan Ilmu Pengobatan, 2018)
Diabetes mellitus (DM) is a chronic disorder that specifically involves the metabolism of carbohydrates (glucose) in the body, also causes disorders of fat and protein metabolism. The benefits of kersen (Muntingia calabura L.) which are well known, among others, overcome DM. This study was conducted to determine the hypoglycemic activity of ethanol extract of M. calabura leaves in reducing blood sugar levels and effective dose of reducing blood glucose in mice (Mus musculus) induced by alloxan 130 mg/kg BW. Distribution of experimental animals, group I was given a glibenclamide suspension 0.13 mg/kg BW as (positive control), groups II, III and IV were given ethanol extract of M. calabura leaves at a dose of 50, 100 and 150 mg/kg BW and the group V is given a 1% NaCMC suspension (negative control). Giving extracts carried out for 7 days. The results showed blood sugar levels before treatment, after induction, and after treatment, respectively, group I (81.00; 141.00; and 94.75 mg/dL), group II (79.00; 138.50; and 50.00 mg/dL), group III (102.50; 119.25; and 77.75 mg/dL), group IV (88.25; 146.00; and 61.00 mg/dL), and group V (108.00; 131.25; and 114.75 mg/dL). Based on the results of the study showed a decrease in blood sugar levels at all doses of ethanol extract of M. calabura leaves which has the potential as a diabetes drug.